The creation and resolution of working hour discrepancies over the life course - Enzo Weber; Franziska Zimmert (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
Studies on labor supply have increasingly taken account of not only the actual working hours, but also of working hour preferences as well as the discrepancy between them. However, longitudinal research on this topic remains scarce. This paper contributes to the analysis of working hour discrepancies by exploring how hours mismatch emerges and resolves with special consideration of the household context. We use a rich longitudinal data set, the German Socio-economic panel (GSOEP), for a discrete duration analysis applying a fixed effects-logit estimator. With special consideration of the household context, the findings suggest that female underemployment is strongly related to household responsibilities impeding the mismatch resolution. On the contrary, the creation of female overemployment is linked to higher qualification and job autonomy. In those positions working hour discrepancies also turn out to be persistent. Male hour constraints can be associated to job positions in a similar way. Nevertheless, the results also show that household responsibilities are less important for both male under- and overemployed. – – Das Arbeitsangebot wird zunehmend nicht nur unter dem Aspekt der tatsächlichen Arbeitszeit, sondern auch hinsichtlich der gewünschten Arbeitszeit und deren Diskrepanz untersucht. Jedoch berücksichtigen nur wenige Studien dieses Thema im Längsschnitt. Dieses Papier trägt zur Analyse von Arbeitszeitdiskrepanzen bei, indem deren Entwicklung, das heißt, deren Entstehung und Lösung beleuchtet wird. Das deutsche Sozio-oekonomische Panel dient als Datengrundlage, um dieser Forschungsfrage mit einer diskreten Verweildauerananlyse unter Verwendung eines Logit-Schätzers, der für individuenspezifische fixe Effekte kontrolliert, nachzugehen. Unter besonderer Berücksichtigung des Haushaltskontextes deuten die Ergebnisse darauf hin, dass Unterbeschäftigung von Frauen stark mit Tätigkeiten im Haushalt korreliert, die die Lösung der Diskrepanz verhindern. Im Gegensatz dazu ist die Entstehung weiblicher Überbeschäftigung mit höheren Bildungsabschlüssen und größerer beruflicher Autonomie verknüpft. In diesen Positionen ist die Überschäftigung auch persistent. Arbeitszeitdiskrepanzen von Männern können auf ähnliche Weise mit beruflichen Positionen erklärt werden. Jedoch sind für die Unter- und Überbeschäftigung von Männern Aufgaben innerhalb des Haushalts und der Familie weniger bedeutend.
Keywords: J21; J22; C23; C41; 330; Working hour preferences; working hour discrepancies; household context; life course; Germany